Zinc finger protein genes from Cucurbita pepo are promising tools for conferring non-Cucurbitaceae plants with ability to accumulate persistent organic pollutants. (March 2015) - Inui, Hideyuki; Hirota, Matashi; Goto, Junya; Yoshihara, Ryouhei; Kodama, Noriko; Matsui, Tomomi; Yamazaki, Kiyoshi; Eun, Heesoo
Graphical abstract: Highlights: Zinc finger protein ( ZFP ) genes are highly expressed in high accumulators of dioxins. There are two types of ZFPs, PBG and BG, in Cucurbita pepo . Expression of ZFP in transgenic tobacco plants brought high accumulation of dioxins. Abstract: Some cultivars of cucumbers, melons, pumpkins, and zucchini, which are members of the Cucurbitaceae family, are uniquely subject to contamination by hydrophobic pollutants such as the organohalogen insecticides DDT. However, the molecular mechanisms for the accumulation of these pollutants in cucurbits have not been determined. Here, cDNA subtraction analysis of Cucurbita pepo cultivars that are low and high accumulators of hydrophobic contaminants revealed that a gene for zinc finger proteins (ZFPs) are preferentially expressed in high accumulators. The cloned CpZFP genes were classified into 2 types: (1) the PBG type, which were expressed in C . pepo cultivars Patty Green, Black Beauty, and Gold Rush, and (2) the BG type, which were expressed in Black Beauty and Gold Rush. Expression of these CpZFP genes in transgenic tobacco plants carrying an aryl hydrocarbon receptor-based inducible gene expression system significantly induced β-glucuronidase activity when the plants were treated with a polychlorinated biphenyl (PCB) compound, indicating that highly hydrophobic PCBs accumulated in the plants. In transgenic tobacco plants carrying CpZFPs, accumulation of dioxins and dioxin-like compounds increased in their aerial parts when they were cultivated in the dioxin-contaminated soil. In summary, we propose that addition of CpZFP genes is a promising tool for conferring noncucurbits with the ability to accumulate hydrophobic contaminants.